Media dan monopoli dagang; Percetakan dan penerbitan di Indonesia pada masa VOC - Kasijanto, Kasijanto (Wacana, Journal of the Humanities of Indonesia, 2008)
This article addresses the research on media history in Indonesia. The VOC (Vereenigde Oost-Indische Compagnie) period of the seventeenth/eighteenth century, also known as the early modern period, is regarded as a starting point in this study. It was during this time that printing machines were imported from Europe by the VOC authorities. The availability of paper and printing ink also made it possible for the production of printed matter such as forms, books, and other material. The first known printed media was the Bataviasche Nouvelles, which served as a kind of newspaper. This period saw three types of publishing houses: (1) urban publishing; (2) publishing houses working under contract; and (3) royal publishing houses. Basically however, all these different publishing activities were aimed at supporting the existence of the VOC. Publishing companies were generally engaged in providing service to the Church and meeting the VOC's administrative requirements. Communication media, based on enhancing freedom of opinion and disseminating information, would pose a problem as it would come face to face with VOC's power monopoly.